POLICY ANALYSIS ON THE APPOINTMENT OF HONORARY TEACHERS AS ASN PPPK: IMPLICATIONS FOR EDUCATIONAL HUMAN RESOURCE STABILITY AND LANGUAGE EDUCATION IN KELUMPANG HILIR DISTRICT - Tataq Harjuna Piranggada; Muhammad Triyoso; Muhsinin; Sahdat; Ahmad Suriansyah; Ratna Purwanti (Universitas PGRI Palembang, 2025)
This study explores the implementation of the policy on appointing honorary teachers as ASN PPPK (Government Employees with Work Agreements) in Kelumpang Hilir District, which faces numerous structural, administrative, and resource-related challenges. The main obstacles identified include limited budget allocations, weak inter-agency coordination, and social resistance from some honorary teachers who perceive the selection process as unfair. Nevertheless, this policy holds significant potential to enhance educational quality, teacher professionalism, and equitable teacher distribution in remote areas. The study highlights the critical role of local governments in supporting the policy's execution by improving coordination mechanisms, ensuring efficient budget management, and delivering clear public outreach. Moreover, strengthening personnel information systems and conducting regular policy evaluations are essential to ensuring its effectiveness. The findings aim to offer practical recommendations for policymakers to overcome existing barriers and support the long-term success of honorary teacher appointments, particularly in stabilizing educational human resources and improving language education quality.